2009
DOI: 10.1016/j.physrep.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

θ dependence of SU(N) gauge theories in the presence of a topological term

Abstract: We review results concerning the θ dependence of 4D SU (N ) gauge theories and QCD, where θ is the coefficient of the CP-violating topological term in the Lagrangian. In particular, we discuss θ dependence in the large-N limit.Most results have been obtained within the lattice formulation of the theory via numerical simulations. We review results at zero and finite temperature. We show that the results support the scenario obtained by general large-N scaling arguments, and in particular the Witten-Veneziano me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
317
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(343 citation statements)
references
References 597 publications
(1,101 reference statements)
26
317
0
Order By: Relevance
“…This is the reason why on the Lattice one can extract results only up to few terms in the expansion around θ = 0, either analytically continuing from imaginary θ values or computing certain correlators at θ = 0. See [1] for an excellent review on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why on the Lattice one can extract results only up to few terms in the expansion around θ = 0, either analytically continuing from imaginary θ values or computing certain correlators at θ = 0. See [1] for an excellent review on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, a possible partial solution is to study the theory at imaginary µ B , where the sign problem disappears, and then make use of analytic continuation to infer the dependence at real µ B , at least for small values of µ B /T [4]. An analogous approach has been proposed for exploring a non-zero θ [5-8]; as for µ B = 0, also in this case one assumes that the theory is analytic around θ = 0, a fact supported by our present knowledge about free energy derivatives at θ = 0 [9,10].Various studies have shown that the dependence of the critical temperature on the baryon chemical potential, T c (µ B ), can be determined reliably up to the quadratic order in µ B , while ambiguities related to the procedure of analytic continuation may affect higher order terms [11]. It is natural to assume that a similar scenario takes place for analytic continuation from an imaginary θ ≡ iθ I term, i.e.…”
mentioning
confidence: 99%
“…After 10-15 years of exploratory computations with cooling techniques, well summarized in Ref. [25], a theoretically well defined definition of the cumulants of the topological charge was found [26,27,28,29,30,31]. The value of the topological susceptibility obtained with the Neuberger definition of the charge [32] indeed supports the Witten-Veneziano explanation for the large experimental value of the η ′ mass.…”
Section: Introductionmentioning
confidence: 53%